Correlation between dominant bacterial community and non-volatile organic compounds during the fermentation of shrimp sauces - Ruichang Gao; Huijie Liu; Ying Li; Hongying Liu; Yue Zhou; Li Yuan (Food Science and Human Wellness)
Shrimp sauce, one of the traditional salt-fermented food in China, has a unique flavor that is influenced by the resident microflora. The quality of salt-fermented shrimp sauce was evaluated in this work by determining the total volatile basic nitrogen (TVB-N), the amino acid nitrogen (AAN), organic acid, 5'-nucleotide and free amino acids (FAA). Moreover, the dynamics of microbial diversity during processing was investigated by using high-throughput sequencing technology. The results showed that the AAN, TVB-N, organic acid, 5'-nucleotide and FAA content were in range of 0.93–1.42 g/100mL, 49.91–236.27 mg/100mL, 6.65–20.68 mg/mL, 3.51–6.56 mg/mL and 81.27–102.90 mg/mL. Among the microbial diversity found in the shrimp sauce, Tetragenococcus, Flavobacterium, Polaribacter, Haematospirillum and Staphylococcus were the predominant genera. Correlation analysis indicated that the bacteria Tetragenococcus and Staphylococcus were important in the formation of non-volatile compounds. Tetragenococcus positively correlated with a variety of FAAs; Staphylococcus positively correlated with 5'-nucleotides. The analysis indicated that Tetragenococcus and Staphylococcus were the core genera affecting non-volatile components. These findings indicate the dynamics of the bacterial community and non-volatile components inter-relationships during shrimp sauce fermentation and provide a theoretical basis for improving the fermentation process of shrimp sauce.